'The fact that': Stance nouns in disciplinary writing. (October 2015) - Jiang, Feng (Kevin); Hyland, Ken
The linguistic resources used by academic writers to adopt a position and engage with readers, variously described as evaluation, stance and metadiscourse, have attracted considerable attention in recent years. A relatively overlooked means of expressing a stance, however, is through a Noun Complement structure, where a stance head noun takes a nominal complement clause. This pattern allows a writer to front-load attitude meanings and offers an explicit statement of evaluation of the proposition which follows (as in 'The fact that science has a history is not an argument against the possibility of scientific truth'). In this article, we explore the frequencies, forms and functions of this structure in a corpus of 160 research articles across eight disciplines totalling 1.7 million words. Developing a new rhetorically based classification of stance nouns, we show that the structure is not only widely used to express author comment and evaluation, but that it exhibits considerable variation in the way that it is used to build knowledge across different disciplines.